Literature Review: Budaya Lapor untuk Meningkatan Keselamatan Pasien di Rumah Sakit Umum Daerah - Hasti Wulandari; Yuliani Setyaningsih; Syamsulhuda Budi Musthofa (Universitas Malahayati Lampung, 2023)
ABSTRACT Increasing number of patient safety incidents in Indonesia, it is important to raise awareness of various parties about reporting incidents that occur in every hospital to minimize unexpected events. Reporting of incidents in a hospital depends on voluntary reports from employees or hospital staff. The purpose of this study was to obtain data information related to Reporting Culture to improve Patient Safety in Hospitals. The method used in this study is a literature review technique based on data results through a Google Scholars search with the keywords used are Patient Safety Culture, Reporting Culture and Patient Safety, inclusion criteria with research sites in hospitals and published journals within the last 5 years years 2018-2022. The results of the analysis of 10 articles prove that almost all applications of patient safety reporting culture get a good category of 12 variables of patient safety culture, the highest is obtained at the Aji Muhammad Parikesit Tenggarong Hospital with the category of application of 12 good variables. Problems found in the application of patient safety in hospitals are openness and frequency of incident reporting. Good communication is needed that is built by the manager so that the patient reporting culture system can be implemented optimally. The importance of implementing a patient reporting culture as an effort to improve hospital service quality management and prevent incidents from happening again. Keywords: Patient Safety Culture, Report Culture, Patient Safety ABSTRAK Meningkatnya kasus insiden keselamatan pasien di Indonesia sehingga sangat penting kesadaran berbagai pihak akan pelaporan insiden yang terjadi di setiap rumah sakit untuk meminimalisir kejadian yang tidak diharapkan. Pelaporan kejadian dirumah sakit tergantung oleh laporan sukarela dari pegawai atau staf rumah sakit tersebut. Tujuan penelitian ini ingin memperoleh informasi data terkait Budaya Lapor untuk meningkatan Keselamatan Pasien di Rumah Sakit. Metode yang digunakan penelitian adalah teknik literatur review berdasarkan hasil data melalui pencarian Google Scholars dengan kata kunci yang dipakai adalah Budaya Keselamatan Pasien, Budaya Lapor dan Keselamatan Pasien, kriteria inklusi dengan tempat penelitian pada RSUD dan jurnal terpublikasi dalam kurun waktu 5 tahun terakhir tahun 2018-2022. Hasil analisa 10 Artikel membuktikan hampir seluruh penerapan budaya lapor keselamatan pasien mendapatkan kategori baik dari 12 variabel budaya keselamatan pasien, tertinggi didapatkan pada rumah sakit RSUD Aji Muhammad Parikesit Tenggarong dengan kategori penerapan 12 variabel baik. Masalah yang ditemukan pada Penerapan keselamatan pasien dirumah sakit yaitu Keterbukaan dan Frekuensi Pelaporan Insiden. Diperlukan komunikasi baik yang dibangun oleh manajer tujuannya agar sistem budaya lapor pasien dapat terlaksana maksimal. Pentingnya penerapan budaya lapor keselamatan pasien sebagai upaya peningkatkan manajemen mutu pelayanan rumah sakit dan mencegah insiden agar tidak terulang Kembali. Kata Kunci: Budaya Keselamatan Pasien, Budaya Lapor, Keselamatan Pasien